DECISIONS ON SHARE INVESTMENT IN AGRICULTURE SECTOR COMPANIES (CAPM Method Approach) - Unang, Unang; Indra Nur Fadilah; Enok Sumarsih (Jurnal AGRISEP, 2023)
ABSTRACT The agriculture stock market appears to have a bright future. Since the COVID-19 outbreak started, share issuers with investments reliant on agricultural commodities have shown significantly improved performance, which may be evidence of this. The goals of this study were to estimate expected returns, assess risk and return on investment, and classify efficient and inefficient stocks in agricultural sector companies listed on the Indonesia Stock Exchange (IDX). Companies in the agricultural sector that underwent evaluation had comprehensive data that needed to be reviewed between January 2019 and December 2021, and they were listed on the IDX and main listing board. The Capital Asset Pricing Model (CAPM) is a method for evaluating and discouraging individuals from making risky stock market investments. There were 15 companies selected. According to the evaluation's conclusions, 10 companies had stocks that could be purchased because they were inexpensive and efficient, while 5 companies had stocks that could be sold because they were inexpensive and inefficient (overvalued).